Synthesis, Spectral and Thermogravimetric Investigation of Zinc(II) Complex of 8-Hydroxyquinoline-5-sulphonic Acid - SOBHANA, D. (Asian Journal of Chemistry, 2010)
Zinc(II) complex of 8-hydroxyquinoline-5-sulphonic acid is synthesized by the reaction of zinc(II) ion with this ligand at the pH of 4.5. The yellow crystalline complex thus formed is characterized by elemental analysis, thermogravimetric and spectral studies viz., UV-Vis, FTIR, 1H NMR and 13C NMR. 8-Hydroxyquinoline-5-sulphonic acid acts as a neutral bidentate ligand coordinating through N- and O-atoms. The complex is diamagnetic and tetrahedral. The structure and geometry of the complex is discussed.